2020
DOI: 10.13057/biodiv/d210404
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity of crude bacteriocin produced by lactic acid bacteria isolated from dadih against Listeria monocytogenes

Abstract: The use of natural preservatives called bacteriocin derived from lactic acid bacteria (LAB) is one way of preventing food from being contaminated by pathogenic microorganisms such as L. monocytogenes (LM). The aims of this study were to evaluate the ability of LAB isolated from dadih to inhibit the growth of LM and to obtain the antimicrobial components that play a role in inhibiting the growth of LM. The antimicrobial activity of the supernatant obtained from 12 strains of dadih LAB was determined using the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 37 publications
2
25
0
1
Order By: Relevance
“…Similarly, some researchers reported that bacteriocin isolated from various fermented foods can suppress S. aureus growth (Abanoz & Kunduhoglu, 2018). The greatest antimicrobial activity against S. aureus was found in R-55, which showed high antimicrobial activity against Listeria monocytogenes, but it showed relatively low antimicrobial activity against E. coli (Pato et al, 2020). This fact indicated that the R-55 strain selectively has a higher antimicrobial activity against gram-positive bacteria than gram-negative bacteria (Bharti et al, 2015;Saeed et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, some researchers reported that bacteriocin isolated from various fermented foods can suppress S. aureus growth (Abanoz & Kunduhoglu, 2018). The greatest antimicrobial activity against S. aureus was found in R-55, which showed high antimicrobial activity against Listeria monocytogenes, but it showed relatively low antimicrobial activity against E. coli (Pato et al, 2020). This fact indicated that the R-55 strain selectively has a higher antimicrobial activity against gram-positive bacteria than gram-negative bacteria (Bharti et al, 2015;Saeed et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
“…The activation of LAB and S. aureus cultures was carried out according to the method described in our previous work (Pato et al, 2020). Each LAB culture was taken as much as 0.1 mL and put into a test tube containing 5 mL MRSB, then shaken evenly and incubated aerobically for 18 h at 37 °C.…”
Section: Activation Of the Lab Culture And Staphylococcus Aureus Fncc-15mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the beneficial antimicrobial properties from bacteriocin of LAB from dadih, it can be used as a natural preservative to prevent food-borne disease [61], including as a natural preservative of chicken meat [62].…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…Vila et al (2010) previously reported that some species of LAB produced enough hydrogen peroxide to inhibit the 3002 growth and action of various microorganisms. Lactobacillus acidophilus produces acidophilin and acidolin, whereas L. plantarum produces bacteriocin (Pato et al 2020, Aritonang et al 2019. Nisin and diplococcin are among some of the antibiotics produced by Streptococci.…”
Section: Introductionmentioning
confidence: 99%